Mixotrophic cultivation of Scenedesmus dimorphus in sugarcane bagasse hydrolysate. Issue 2 (27th August 2019) - Manzoor, Maleeha; Ahmad, Qurat‐ul‐Ain; Aslam, Ambreen; Jabeen, Faiza; Rasul, Azhar; Schenk, Peer M.; Qazi, Javed I.
Abstract: Overuse of the fossil fuels to fulfill existing energy requirements has generated various environmental problems like global warming. Emergence of environmental issues due to burning of the fossil fuel resources has provoked researchers to explore alternative sources of fuel. In this scenario, microalgal biofuels could present a promising alternative fuel if produced cost‐effectively without competing for freshwater resources and arable land. Aim of the present study was to grow microalgae by employing lignocellulosic waste for production of lipids. Scenedesmus dimorphus NT8c was chosen based on its ability to tolerate heat, rapid growth, and ease of harvesting by overnight settling. Biochemical composition and growth parameters of microalgae were analyzed when cultivated mixotrophically on sugarcane bagasse hydrolysate, a low‐value agricultural by‐product, that is, currently underutilized. Despite a slight increase in turbidity in the medium, S. dimorphus NT8c cultures raised mixotrophically in 5 g/L sugarcane bagasse hydrolysate displayed significantly higher growth rates compared to photoautotrophic cultivation with an overall biomass productivity of 119.5 mg L d −1, protein contents of 34.82% and fatty acid contents of 15.41%. Thus, microalgae cultivated mixotrophically are capable of photosynthesizing while metabolizing and assimilating organic carbon, significant increases of biomass and lipid productivity can be achieved. However, high supplementation with organic carbon can result in unfavorable levels of turbidity and bacterial growth, reducing microalgal biomass productivity.